2011
DOI: 10.1017/s1365100510000830
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Policy, Education and Growth: A Reappraisal When Lifetime Is Finite

Abstract: This article demonstrates that when finite lifetime is introduced in a Lucas (1988) growth model where the source of pollution is physical capital, the environmental policy may enhance the growth rate of a market economy, while pollution does not influence educational activities, labor supply is not elastic and human capital does not enter the utility function. The result arises from the "generational turnover effect" due to finite lifetime. It remains valid under conditions when the education sector uses fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…This growth can be sustainable because the price of pollution permits evolves at the same growth rate as the stock of physical capital. This result holds on previous studies (e.g., Hettich, 1998; Pautrel, 2008, 2009, 2012), following the pollution function considered by Gradus and Smulders (1993). Defining φ as the pollution elasticities of capital, previous studies are derived equation (6) as follows: Pt=[]φτtPKtφ/1+φ,…”
Section: The Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…This growth can be sustainable because the price of pollution permits evolves at the same growth rate as the stock of physical capital. This result holds on previous studies (e.g., Hettich, 1998; Pautrel, 2008, 2009, 2012), following the pollution function considered by Gradus and Smulders (1993). Defining φ as the pollution elasticities of capital, previous studies are derived equation (6) as follows: Pt=[]φτtPKtφ/1+φ,…”
Section: The Modelsupporting
confidence: 90%
“…To this research question, Hettich (1998) and Pautrel (2008, 2012) answer yes because they found that an increase in the environmental tax rate reduced pollution and a rise in economic growth rate, analysing the Uzawa‐Lucas model. Endogenous labour supply considered by Hettich (1998) and infinity of household lifespan considered by Pautrel (2008, 2012) have essential roles on the growth‐enhancing effect of environmental policy. Especially, the former study implies an importance of household's preference on growth‐enhancing effect of environmental policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of environmental awareness on growth differs from the one generally detected in the literature. Gradus and Smulders (1993), Vellinga (1999), and Pautrel (2011) have shown that the long-run growth rate is independent of the degree of environmental concern. In their setting, the negative impact of greener preferences on physical capital accumulation (the polluting input) is exactly offset by the greater incentive to accumulate human capital (the clean input).…”
Section: Comparative Staticsmentioning
confidence: 99%
“…Vellinga (1999) gets the same result with a model extended by a stock of pollutant and with separability in utility between consumption and the environment. Within an overlapping-generations modelà la Blanchard (1985), Pautrel (2011) asks whether environmental policy may have a positive impact on long-term growth. In his setting the growth rate of the economy depends on the environmental tax.…”
Section: Introductionmentioning
confidence: 99%